Water Requirement for Recycled Concrete - Kirgiz, Mehmet Serkan; Kırgız, Mehmet Serkan (Elsevier, 2021)
This chapter is aimed at informing university and college students regarding the water requirement of recycled concrete aggregate (RCA) with an emphasis on the use of the RCA in professional practice. Owing to the increasing demand of RCA worldwide, there has to take sufficient care to ensure the selection of correct ingredients for the manufacture of recycled aggregate concrete (RAC). Indeed, the effects of water requirement of RCA is as high as not to be taken into account, as the RCA is covered mortar (CM) in its own parent fundamentally. The quality of RCA depends on its parent resource produced as well. To ensure the structural integrity of the RAC structure, the structural designer, the contractor, the enterprise, and the practitioner have to get rid of its mortar covered. The chapter, in accordance with the content of the book, is well advised to cope with the CM in the RCA.
Water Requirement for Recycled Concrete / Editors:Paul O. Awoyera, Carlos Thomas, Mehmet Serkan Kirgiz -- Elsevier -- ISBN:978-012824105-9 -- 2021.